Perancangan green packaging pada produk air minum dalam kemasan (AMDK) menggunakan metode conjoint analysis - Ilyas Ilyas; Sarika Zuhri; Didi Asmadi; Fajri Maulida (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Bottled Drinking Water is the everyday primary need of living things. This product produces a lot of waste, so an alternative is needed to minimize the amount of waste of the product with eco friendly packaging (green packaging). The consumers' assessments are needed to see how green packaging fit their preferences. This study uses Conjoint Analysis as method with 100 respondents in total. Based on the first stage of questionnaire distribution, there are 27 stimulus cards consist of 10 attributes and 32 levels that will be assessed by respondents at the second stage. The results of consumers' preferences show that color is the attribute which influence consumers' desicions the most in noticing bottled drinking water using green packaging with the highest utility value of 13.58 %. The results also showed that the 20th stimulus card was the most representative card of respondents' preferences with utility value of 0.158. Attributes, levels, and utility values selected on this card are green color of 0.003, ergonomic packaging design of 0.029, complete product information of 0.027, packaging technology using recyclable material (biodegradable formula) of 0.025, packaging material from coconut fiber (cocofibre) of 0.015, straw material from paper of 0.006, low prices of 0.035, brand availability of 0.004, packaging in 220 ml size of 0.008 and the beautiful earth as logo (graphic design) of 0.006. The results of this research was expected to be a reference for the latest green packaging design according to Sustainable Development Goals (SDGs) concept.